Extrinsic doping of the half-Heusler compounds. (8th July 2016) - Stern, Robin; Dongre, Bonny; Madsen, Georg K H
Abstract: Controlling the p- and n-type doping is a key tool to improve the power-factor of thermoelectric materials. In the present work we provide a detailed understanding of the defect thermochemistry in half-Heusler compounds. We calculate the formation energies of intrinsic and extrinsic defects in state of the art n-type TiNiSn and p-type TiCoSb thermoelectric materials. It is shown how the incorporation of online repositories can reduce the workload in these calculations. In TiNiSn we find that Ni- and Ti-interstitial defects play a crucial role in the carrier concentration of TiNiSn. Furthermore, we find that extrinsic doping with Sb can substantially enhance the carrier concentration, in agreement with experiment. In case of TiCoSb, we find ScTi, FeCo and SnSb being possible p-type dopants. While experimental work has mainly focussed on Sn-doping of the Sb site, the present result underlines the possibility to p-dope TiCoSb on all lattice sites.